A Confirmed Case of Ignatzschineria larvae Bacteremia From a Myiatic Wound Infection in Kentucky - Meredith L. Johnson; Blakely Kennedy; Patricia A. Santos (Annals of Internal Medicine: Clinical Cases)
Myiasis, or the infection of a fly larva (maggot) in a human tissue is a rare occurrence in the United States. Rarer yet is bacteremia arising from such infection. In this case report, we discuss a case of Ignatzschineria larvae bacteremia that we believe is only the second of its kind reported in the United States, both being from the state of Kentucky. We provide more information regarding exposure, risk factors, and clinical manifestations of the disease, along with insight into the pharmacologic approach to treatment based on known susceptibilities.